The Effect of Binahong Leaf Extract Emulsion (Anredera cordifolia) on Histopathological Description of Common Carotid Artery Study on Male Wistar (Rattus novergicus) Rats Induced by Diabetes Mellitus Using Streptozotocin - Fauzi, Muhammad Iqbal; Pudjonarko, Dwi; Indraswari, Darmawati Ayu; Istiadi, Hermawan; Wati, Arinta Puspita (Faculty of Medicine, Diponegoro University, 2024)
Background: Diabetes mellitus (DM) is a chronic metabolic disease that can cause microvascular and macrovascular complications. The formation of superoxide (O2-) by dysfunctional mitochondria in diabetes has been recognised as a major driver of diabetic complications. Consequently, the utilisation of antioxidants may prove advantageous. The plant Andredera cordifolia contains flavonoids, which act as antioxidants.Objective : to investigate the effect of binahong leaf extract on the development of atherosclerosis in the carotid artery.Methods: The research employed a laboratory experimental method with a randomised post-test control group design. The research subjects were 15 Wistar rats (Rattus norvegicus). In this research, the extraction of the active compounds was achieved through a maceration process using 96% ethanol (1:3) and emulsification by the addition of sunflower oil, CMC, Span80 and Tween 20. The analysis of Anredera cordifolia extract content included the determination of flavonoid content and IC50. The intervention will be conducted for a period of 14 days. The rats were administered 1 ml of aquades per day, 45 mg/kg BW of metformin (K+), 200 mg/kg BW of EAC (P1), and 400 mg/kg BW of EAC (P2). The diabetic model was induced using a single dose of 50 mg/kgBW streptozotocin intraperitoneally. On the fourteenth day following the induction of treatment, blood glucose measurements were taken using the GOD-PAP method, and a histopathological examination of the common carotid artery was conducted using eosin haematoxylin staining at a magnification of 100-400x.Results: The total flavonoid content of binahong leaves is 1525 mg/100 g extract, while the IC50 value is 1.9 ppm. The results of the ANOVA indicate a statistically significant difference between the fasting blood glucose levels of the two groups (p < 0.05). The post hoc test demonstrated that a 400 mg/kgBW dose can result in a reduction in glucose levels to 305.75 mg/dl, with a p-value of 0.001 (p < 0.05). The Mann-Whitney test revealed a statistically significant difference among the groups (p < 0.05) for the inhibition of atherosclerosis in the common carotid artery. Conclusion: A significant difference was observed in the administration of 400 mg/kgBB binahong leaf emulsion extract in comparison to a negative control group, with regard to the histopathological picture of atherosclerosis of the common carotid artery